Algoritmo evolutivo de cromossomo duplo para calibração multivariada - Santiago, Kelton de Sousa (2013)
samples and variables selection simultaneously. The algorithmic methods combination for selecting samples and variables in the multivariate calibration aims to building an effective model for predicting the concentration of a certain interest property. As study case uses data acquired by a material analysis with near infrared waves (NIR) on wheat samples in order to estimate the proteins concentration. The algorithms for selection samples as the random number generator (RNG), KennardStone (KS), sample set partitioning based on joint X and Y (SPXY) were used in conjunction with successive projection algorithms (SPA) and partial least square algorithm (PLS) for selection of variables in order to obtain results that can be used for comparison basis with the proposed algorithm AGCD results obtained. The presented results by samples selection algorithms (GNA, KS and SPXY) were too close,butwhenusedtogetherwithvariableselectionalgorithms(SPAandPLS)theresults were better in RMSEP terms. TheAGCDachievedsigniﬁcantlybetterresultscomparedtotheotherstestedalgorithms, reaching an improvement of 97% in comparison with the KS algorithm and an improvement of 63% over SPXY-PLS algorithm, which further approached the AGCD results.